Early asiatic migration to the Americas: a view from South America - Politis, Gustavo Gabriel (2015)
During last three decades, American archaeology has generated a large body of information, which has fuelled debate on the early peopling of the New World. This has allowed scientists to propose and validate macro-regional (continental) dispersal models, empirically grounded in multiple lines of evidence. On the basis of reviewing archaeological and bioarchaeological data, and emphasizing the southern South American information, we summarize and discuss the main topics of the current debate. We presently consider that the first humans arrived on the northern continent from the Asian northwest some time at the end of the Pleistocene, approximately 15,000–14,000 ¹⁴C years BP. A short time later (ca. 12,500 ¹⁴C years), they had already reached the Southern Cone of South America.